Health System Impacts of Skin-Lightening Practices: A Scoping Review of Sub-Saharan Africa and Case Study of Senegalese Women - Kandé, Inna Fatoumata (Université d'Ottawa / University of Ottawa, 2022)
Background and objectives This research explores the trend of skin-lightening in Senegal from an experiential and health systems perspective. Skin-lightening - a practice mostly done by women consisting of topically applying lightening products - is a widespread trend in Senegal, a country still grappling with a colonial legacy of racism and colorism. Although there is growing research on the health impacts of this practice, the impact of widespread skin-lightening practices from a health system perspective remains scarcely explored. Approach The main research question is, “what are the health system impacts of skin-lightening trends among Senegalese women?” Three sub-questions were addressed: 1. What are the key health and health care implications of the use of skin-lightening products as identified in the literature? 2. How do these health and health care implications influence the skin-lightening practices of Senegalese women? 3. How can this knowledge inform health care decision-makers in Senegal? A multi-phased approach consisted first of a scoping review on the topic and second, in-depth interviews with 13 Senegalese women to gather insights on skin-lightening practices and their health system implications. Results The findings from the two methodological approaches addressed three main themes: motivations, practices, and effects. Negative and positive motivations for the practice of skin-lightening emerged with some overlapping and nuanced factors which highlighted the complex reality of skin-lightening trends. Skin-lightening practices included two influences: community practices and personal practices of women interviewed. It appears that skin-lightening in sub-Saharan Africa can often be associated with age as it seems to greatly affect younger women. Finally, insights on the effects of skin-lightening highlighted many dermatological problems. Other health concerns were also mentioned including some mental health problems which emphasized dissatisfaction with the practice for long-term users of skin-lightening products. Conclusion The knowledge generated from this research highlights existing misconceptions regarding skin-lightening trends in the community. It can support a more informed health system response to the utilization of skin-lightening products and help develop evidence-informed guidance for all relevant actors in this practice
Keywords: skin-lightening